Analysis of IoT Implementation to Optimize the Quality Control System for the Installation of the PJUTS Project at PT. Industri Telekomunikasi Indonesia (Persero) - Danillah, Fadlan Dafa; Anjar Priyono (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to analyze the implementation of the Internet of Things (IoT) in optimizing the quality control (QC) system in the Solar Public Street Lighting (PJUTS) project, with a case study at PT Industri Telekomunikasi Indonesia (Persero). The approach used is qualitative, with data collection techniques in the form of observation, in-depth interviews, and documentation during the internship at the company. The results showed that the use of Internet of Things (IoT) technology such as GPS-based cameras, Looker Studio, My Maps, Google Drive, and Spreadsheet can improve the efficiency and effectiveness of the QC process by using a cloud- based monitoring and documentation system. However, there are some constraints that need to be considered when adapting the technology and validating field data. Overall, the application of IoT improves the quality of project supervision and enhances the competitiveness of companies in Industry 5.0.